The 2019 updated EULAR/ERA-EDTA guidelines for the management of lupus nephritis. Expert comments. Part I - N. L. Kozlovskaya; S. K. Solovyev; E. A. Aseeva; T. V. Popkova; T. A. Panafidina; E. L. Nasonov; A. M. Lila; A. A. Mesnyankina; N. Yu. Nikishina (Современная ревматология)
The paper presents the main provisions of the 2019 updated European League Against Rheumatism (EULAR)/European Renal Association (ERA) – European Dialysis and Transplant Association (EDTA) guidelines for the management of lupus nephritis. It discusses the technology of preparing recommendations by an international group of rheumatologists, nephrologists, morphologists, and pediatricians. The main part contains recommendations on the use of induction and maintenance therapy with immunosuppressants, glucocorticoids, and biological agents. The issues relating to the management of pregnant patients with end-stage renal failure are considered.